Simulador para treinamento de cadeirantes em ambiente virtual acionado por comandos musculares e/ou visuais - Martins, Felipe Roque (2017)
The act of driving an electric-powered wheelchair seems, at first glance, a simple task to perform. In reality, however, the ability to conduct a wheelchair independently requires specific motor, visual and cognitive abilities, and attempting to perform such an act without adequate preparation and knowledge may pose a risk, not only for the user in question, but also to the individuals at close proximity. In this perspective, the present work proposes a tool for training and adaptation of users of electric-powered wheelchairs, a simulator aimed mainly at users with little experience with such device, through use of Virtual Reality. By using this simulator, it might be possible to assist in the process of adapting to the new technology and in acquiring knowledge of how to act in some situations, effectively preparing the new user how to deal with different contexts while driving his electric-powered wheelchair. For the development of this work, a survey was first made with experienced users of electric-powered wheelchairs to discover the main needs and difficulties in driving a wheelchair. After that, a virtual environment was created using the Unity 3D tool, in which three distinct scenarios were initially designed based on the survey results. As of the form of control, three different forms were adapted, so that the simulator also could be used for individuals with severe motor disabilities. Finally, it was done a case study with four users in order to evaluate the tool, both in terms of realism and immersion, as well as in practical utility. In the long term, it is expected that the tool can be used by individuals to train their ability to drive electric-powered wheelchairs effectively and in a completely safe environment.